The multicultural cookbook for students - Albyn, Carole Lisa.; Webb, Lois Sinaiko (Phoenix, Ariz. : Oryx Press, 1993)
Presents a collection of recipes from over 120 countries and briefly discusses the culture and culinary habits of each country.
Includes index.
Keywords: International cooking -- Juvenile literature; Food habits -- Juvenile literature; Food crops -- Juvenile literature; International cooking; Food habits